The Impact of Perceived Employability on The Employment Quality of Management Graduates: The Mediating Role of Focused Job Search - Gupta, Ruchika; Ansari, Amirul Hasan (Universiti Utara Malaysia Press, 2023)
Gaining quality employment as the outcome of an exhaustive job search process apparently has no clear pathway for success. With little experience of the job market, young graduates’ initial steps into the complexity of finding the right job essentially need guidance. This study provides insights on how recent management graduates could achieve long-term employment success through factors that would assist them in obtaining quality jobs. A conceptual framework rooted in social-cognitive career theory imparted the present study a twofold purpose of examining the effect of perceived employability (internal and external) and focused job search on employment quality (starting salary and job satisfaction) and investigating the intervening employment quality. A two-wave correlational study was performed which involved 250 recently employed management graduates. The structural equation modelling analysis via Partial Least Square (PLS) found that the internal perceived employability was significantly related to starting salary and job satisfaction. However, the external perceived employability was only significantly related to starting salary. Moreover, a competitive mediation by focused job search showed its negative influence on the relationship between internal perceived employability and starting salary. Finally, the results upheld that employability perceptions and a job search approach are vital aspects to be considered during the university-to-work transition. These insights would assist the career counsellors to instill positive employability perceptions in the focused management graduates to enhance their possibility of obtaining better pay and a more satisfying job.